The Value Stream of Turmeric Curry NongHong Community Enterprise - Phokawattana, Onpawee; Jinachan, Krittika (RMUTL Engineering Journal, 2021)
This research started by collecting information of Nong Hong Turmeric Curry’s supply chain under the concept of value chain management. Then, the value steam mapping was used to categorize the activities, from seed procurement to placing the label on to product. The result shows that there are non-valued activities, both necessary and unnecessary, at the ratio of percent 79.73. The methods for reducing these non-valued time were suggested in 2 ways. First, eliminate the duplicated, unvalued activities which is the quality inspection activity. Second, an increasing percentage of contact farming was suggested in order to reduce time during the production preparation activity. The reduction of time in non-valued activities was analyzed using simulation method. The result shows that the average total cycle time of process in Nong Hong Turmeric Curry supply chain from seed procurement to placing the label on to product decreased 9.84 hours from 268.49 to 258.65, or 3.00 percent. The result is to promoted for increase the ratio of contact farming from 10 percent to 50 percent that can reduce time during the production preparation activity.